2010
DOI: 10.1097/bpb.0b013e3283303392
|View full text |Cite
|
Sign up to set email alerts
|

Large suprapatellar synovial cyst in a 12-year-old girl: arthroscopic decompression

Abstract: In this study, we present a case of a very rare and large suprapatellar synovial cyst of the knee, which was successfully treated with an arthroscopic intra-articular decompression. Suprapatellar bursa is located between the femur and quadriceps tendon, proximal to the knee joint, and it normally communicates with a joint cavity. However, very rarely bursa can remain completely separated from the knee joint, which can result in the formation of a separated compartment inside which, in special circumstances, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…2,6,10,16 It is believed that cyst formation depends on a connection between the joint and bursa, with a valve-like effect allowing the passage of fluid from the joint into the bursa with subsequent distention, producing these cysts. 2 Intra-articular cyst decompression relies on resection of the connecting valvular mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,6,10,16 It is believed that cyst formation depends on a connection between the joint and bursa, with a valve-like effect allowing the passage of fluid from the joint into the bursa with subsequent distention, producing these cysts. 2 Intra-articular cyst decompression relies on resection of the connecting valvular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Open resection is commonly performed for symptomatic synovial cysts. 3,5,[8][9][10][11][12] Because of the strong association of intra-articular pathologies with these cysts, knee arthroscopy and treatment of the intra-articular pathologies have become trends and there has been an increase in surgeons' interest in treating these cysts arthroscopically. 5,13,14 Arthroscopic treatment is indicated when there is intra-articular communication and associated joint disorder because these lesions can be treated to obliterate the cysts and prevent their recurrence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crnkovic et al 2 have described an isolated suprapatellar cyst in a 12-year-old girl that showed similarities with Baker's cist just because of the existence of valve communication between the joint and the cyst (Figure 4A,B).…”
Section: Anatomy and Etiologymentioning
confidence: 99%
“…They are usually presented with palpabile mass, pain, limited range of movement or they can be asymptomatic, accidentaly discovered by magnetic resonance imaging (MRI) after a knee injury. 1,2 Although cystic masses like popliteal cyst, cyst of the medial and lateral meniscus are very well described in orthopaedic literature, there are few written reports of isolated suprapatellar bursitis or cyst. In general, bursae are anatomic structures located between the bone surface and tendon and ligaments that reduce the friction between these moving structures.…”
Section: Introductionmentioning
confidence: 99%